Location and direction specificity in motion direction learning associated with a single-level method of constant stimuli - Xiong, Y. Z.; Xie, X. Y.; C. Yu (Vision Research, 2016)
Practice improves discrimination of many basic visual features, such as contrast, orientation, and positional offset [1-7]. Perceptual learning of many of these tasks is found to be retinal location specific, in that learning transfers little to an untrained retinal location [1, 6-8]. In most perceptual learning models, this location specificity is interpreted as a pointer to a retinotopic early visual cortical locus of learning [1, 6-11]. Alternatively, an untested hypothesis is that learning could occur in a central site, but it consists of two separate aspects: learning to discriminate a specific stimulus feature ("feature learning"), and learning to deal with stimulus-nonspecific factors like local noise at the stimulus location ("location learning") [12]. Therefore, learning is not transferable to a new location that has never been location trained. To test this hypothesis, we developed a novel double-training paradigm that employed conventional feature training (e.g., contrast) at one location, and additional training with an irrelevant feature/task (e.g., orientation) at a second location, either simultaneously or at a different time. Our results showed that this additional location training enabled a complete transfer of feature learning (e.g., contrast) to the second location. This finding challenges location specificity and its inferred cortical retinotopy as central concepts to many perceptual-learning models and suggests that perceptual learning involves higher nonretinotopic brain areas that enable location transfer.